THE CITY AS AUTOBIOGRAPHY : The Self and The City as Reflexive Projects - Voragen, Roy (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
The self and the city interrelate; both the self and the city arereflexive projects. Moreover, these reflexive projects aredialectally interrelated. Identity is not expressed in actions but(per-)formed through actions. Performativity entails a dialogue,with others and with the urban environment. The meaning ofthe self is public and shown in its created forms: the city.Knowledge is grounded not in theory but in practice, i.e.knowledge of the city is shown in social practices, styles andforms. The unforeseen and unwanted consequences of theurban risk society cause anxiety, which in turn causessegregation, exclusion and architecture of fear. To overcomethis, we citoyens need creativity as a virtue; the density of amegalopolis could also lead to an innovative attitude, hence theexperiences of the creative communities in Bandung.